The Effect of On Street Parking on Road Performance - Lantang, Evayanti Tirtania; Birawaputra, Indra; Alberto, Alberto (Jurnal Multidisiplin Indonesia, 2025)
Jalan Merdeka is an area that has many shops, restaurants, and hotels, so that many vehicles park on the road (on street parking) which results in traffic being often hampered. This study aims to analyze the influence of on street parking on the performance of road sections, as well as to determine the influence of side obstacles on road performance and service levels. The method used is a direct survey in the field with data on traffic volume, side obstacles, and on street parking. The results showed that the contribution of on street parking (PSV) to the total side barriers only ranged from 10–21%, which indicated that PSV did not significantly reduce the performance of the road. A factor that has a greater influence on road performance is the activity of vehicles entering and exiting (EED). The average level of road service is in category D, while the side obstacle class is included in the VL (very low) category. The implications of these findings suggest that traffic management policies should prioritize the regulation of vehicle access in and out (EED) rather than simply prohibiting parking on the road, as well as opening up opportunities for more structured parking arrangements on these sections.